2015
DOI: 10.15171/hpp.2015.007
|View full text |Cite
|
Sign up to set email alerts
|

Pinch Strengths in Healthy Iranian Children and Young Adult Population

Abstract: Article type: Original ArticleBackground: Data on the physical strength capabilities are essential for designing safe and usable products and are useful in a wide range of clinical settings especially during treatment of disease affecting the function of the hand. The purpose of this study was to determine peak lateral pinch strength, key pinch strength, tip-to-tip pinch strength and three-jaw pinch strength exertions in a healthy Iranian children and young adult population. Methods: The study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…This finding is similar to previous studies on pinch and grip strength in both children and adults. 30,31 Dianat et al 32 compared 4 types of pinch strength between males and females between 7 and 30 years and found that males showed significantly higher strength compared with females in both the dominant and nondominant sides on all 4 strength tests. McQuiddy et al 30 also found that sex is a factor influencing grip and pinch strength in children and adolescents between 6 and 19 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is similar to previous studies on pinch and grip strength in both children and adults. 30,31 Dianat et al 32 compared 4 types of pinch strength between males and females between 7 and 30 years and found that males showed significantly higher strength compared with females in both the dominant and nondominant sides on all 4 strength tests. McQuiddy et al 30 also found that sex is a factor influencing grip and pinch strength in children and adolescents between 6 and 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…This result is inconsistent with previous studies investigating grip and pinch strength in participants from preadolescent to adolescent age and intrinsic hand muscle strength in younger children. 8,30,32,33,38 It is possible that the developmental trajectories of small intrinsic muscles are different from extrinsic muscles and lead to less increase in strength through age. Similar to our findings, Dianat et al 32 found that the pinch strength was not associated with age in participants between 16 and 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to immature pinch grasp in children ages 3 to 6. 20 In addition, the three CUE-T items (2-finger pinch, 3-finger pinch, key pinch) require full development of intrinsic hand function and in-hand manipulation skills, which may not be developed even in typically developing children until 7 years of age. 21,22 For this reason, we suggest that the CUE-T be used in children older than 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…New instruments for the risk assessment of biomechanical overload reported in the recent scientific literature are sEMG and systems of objective measurement of the force in grip or pinch grip [ 20 , 21 , 22 , 23 ]. The main aim of such studies is to evaluate objective tools for biomechanical overload risk assessment but also looking for new limit values for strain exertion [ 24 ] and evaluation of differences in the mean pinch strength values in terms of age and sex [ 25 ].…”
Section: Discussionmentioning
confidence: 99%